Diversification of chiles (Capsicum, Solanaceae) through time and space: New insights from genome-wide RAD-seq data - Carrizo García, Carolina; Barboza, Gloria Estela; Palombo, Nahuel; Weiss-Schneeweiss, Hanna (Frontiers in Genetics, 2022)
Capsicum L. encompasses 43 American species, including the five domesticated worldwide consumed sweet and hot chiles. This study presents new, updated and age-calibrated phylogenetic hypothesis on the genus evolution incorporating nearly all currently accepted Capsicum species. A new model of spatial diversification of Capsicum is proposed based on analyses of several thousands of genome-wide RAD-seq derived SNPs. Maximum likelihood approaches were used to reconstruct phylogenies and to estimate dates of all major splits. Ancestral ranges were inferred and diversification events were modeled in a time frame using a Bayesian approach. Nine clades corresponding to genetically and (mostly) geographically well-defined lineages, which diversified starting around mid-upper Miocene, were recovered with strong support. The Northern and Central Andes were inferred to represent the most likely ancestral range of the genus Capsicum. A few early vicariant and dispersal events were estimated to have driven the geographic divergence of the main Capsicum clades. Each lineage was inferred to have diversified within a distinct region of South America and expanded geographically to different extent. Extant species diversification was inferred to have begun at the beginning of Pliocene and continued through the Pleistocene. The Central Andes, represented mainly by the territory of present-day Bolivia, were proposed to play a central role in the diversification of lineages comprising domesticated capsicums and their wild allies. The genome-wide approach allowed for high resolution and support of deep phylogenetic nodes providing novel insights into the affinities of major lineages and clades as well as on the geographic expansion of Capsicum. This study provides the first dated evolutionary history of the genus encompassing most of the chile species diversity.